2001
DOI: 10.1111/j.1469-7793.2001.00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Group II muscle afferents probably contribute to the medium latency soleus stretch reflex during walking in humans

Abstract: The central nervous system (CNS) takes advantage of a network of complex neural pathways and mechanisms in the control of normal human gait. One such mechanism is the use of afferent feedback from muscle, cutaneous and joint receptors. Our knowledge of the contribution of afferent information in human gait is still limited, although this has been an area of active research for many years (e.g. Dietz et al. 1985;Yang et al. 1991;Sinkjaer et al. 1996). Yang et al. (1991) and Sinkjaer et al. (1996) have shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
164
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(175 citation statements)
references
References 33 publications
9
164
1
1
Order By: Relevance
“…In fact, experiments on interlimb coordination of leg muscle activation have confirmed that unilateral leg displacement during gait evokes a bilateral response pattern, with a similar onset in both sides 3,4 but only when both limbs are performing a supportive role 5,6 . This is consistent with the evidence that a large majority of midlumbar interneurones recipient from group II input are influenced by afferent fibres from both ipsilateral and contralateral sides 7 and by vestibulo-and reticulo-spinal pathways 8 , and with the importance given to medium latency response from group II to feedback in the stance phase of gait 9 .…”
Section: Introductionsupporting
confidence: 75%
“…In fact, experiments on interlimb coordination of leg muscle activation have confirmed that unilateral leg displacement during gait evokes a bilateral response pattern, with a similar onset in both sides 3,4 but only when both limbs are performing a supportive role 5,6 . This is consistent with the evidence that a large majority of midlumbar interneurones recipient from group II input are influenced by afferent fibres from both ipsilateral and contralateral sides 7 and by vestibulo-and reticulo-spinal pathways 8 , and with the importance given to medium latency response from group II to feedback in the stance phase of gait 9 .…”
Section: Introductionsupporting
confidence: 75%
“…These findings correspond to the results of Grey and coworkers, who reported the SLR of the ankle muscle soleus being velocity sensitive while the MLR was not (Grey et al, 2001). These previous results, which were achieved during perturbation of gait, have been confirmed in isolated rotational perturbation of the ankle joint in an ergometer (Gollhofer & Rapp, 1993;Leukel et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…For the ankle joint, it was shown that latency and magnitude of reflex responses are determined by the stretch velocity and the amplitude. For instance, the short latency response (SLR) of the soleus muscle which is considered to be mediated by fast conducting Ia afferent fibers (Bove, Nardone, & Schieppati, 2003;Morin & Pierrot-Deseilligny, 1977), was reported to be sensitive to the stimulus velocity (Gollhofer & Rapp, 1993;Grey, Ladouceur, Andersen, Nielsen, & Sinkjaer, 2001;Leukel et al, 2009). The size of the medium latency response (MLR), on the other hand, was determined by the amplitude of the induced stretch (Gollhofer & Rapp, 1993;Leukel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the muscle is lengthening too rapidly, the velocity term will increase the activation; if it is shortening too quickly, the velocity term will reduce activation. Several empirical studies [12,[34][35][36][37][38] have demonstrated the presence of afferent feedback in the plantar flexors during stance. These studies record the changes in muscle EMG signals when the gait of a subject is perturbed either by changing the inclination of the walking surface or by forcing muscle-tendon length changes using an orthosis.…”
mentioning
confidence: 99%